Influence of galactose cataract on erythrocytic and lenticular glutathione metabolism in albino rats - Jyothi, M (Medknow Publications, 2011)
CONTEXT: Glutathione depletion has been postulated to be the prime reason for galactose cataract. The current research seeks the prospect of targeting erythrocytes to pursue the lens metabolism by studying the glutathione system. AIMS: To study the activity of the glutathione-linked scavenger enzyme system in the erythrocyte and lens of rats with cataract. MATERIALS AND METHODS: Experiments were conducted in 36 male albino rats weighing 80 ± 20 g of 28 days of age. The rats were divided into two major groups, viz. experimental and control. Six rats in each group were sacrificed every 10 days, for 30 days. Cataract was induced in the experimental group by feeding the rats 30% galactose (w/w). The involvement of reduced glutathione (GSH) and the linked enzymes was studied in the erythrocytes and lens of cataractous as well as control rats. STATISTICAL ANALYSIS: Parametric tests like one-way ANOVA and Student's ‘t’ test were used for comparison. Correlation linear plot was used to compare the erythrocyte and lens metabolism. RESULTS: Theconcentration of GSH and the activity of linked enzymes were found decreased with the progression of cataract, and also in comparison to the control. The same linear fashion was also observed in the erythrocytes. CONCLUSION: Depletion of GSH was the prime factor for initiating galactose cataract in the rat model. This depletion may in turn result in enzyme inactivation leading to cross-linking of protein and glycation. The correlation analysis specifies that the biochemical mechanism in the erythrocytes and lens is similar in the rat model.